The Cyclicality of Irish Fiscal Policy Ex-Ante and Ex-Post - Cronin, David; McQuinn, Kieran (The Economic and Social Review, 2018)
The cyclicality of fiscal policy in Ireland in the budgetary plans put before parliament and expost is considered. Data in budgetary documents and particular econometric estimation procedures help address endogeneity issues and provide numerous variable-estimation procedure combinations for assessing cyclicality. Fiscal policy in Ireland is found to be pro-cyclical on both ex-ante and ex-post bases. The evidence is mixed between policy being more pro-cyclical ex-post than was intended at Budget time and there being no difference. With the preventive arm of the Stability and Growth Pact now applying to Ireland, a continuation of pro-cyclical fiscal policy would endanger its requirements being met.